Molecular cloning of Cyclodextrin glucanotransferase gene from Bacillus sp. G1 - Ong, Rui Min (2005)
The Cyclodextrin glucanotransferase (CGTase, EC 2.4.1.19) gene from Bacillus sp. G1 was successfully isolated and sequenced. The 16s rRNA gene sequence of Bacillus sp. G1 was compared with 18 closet neighbours and it exhibited the closest match with that from Bacillus sp. NER (99%). Based on this finding, Bacillus sp. G1 are considered to be a member of the Bacillus rRNA group 5 and identified as Bacillus sp. Determination of the nucleotide sequence revealed the presence of an open reading frame of 2610 bp beginning with a TTG initiation codon which encodes a typical signal peptide of 29 amino acid residues followed by the mature enzyme of 674 amino acid residues. The mature CGTase corresponds to a calculated molecular weight of 75389 Da which is very close to the molecular weight of the wild type Bacillus sp G1 (75kDa) estimated through SDS-Page. A putative Shine-Dalgarno sequence AAGG was located 5 bp upstream of the TTG codon. The deduced amino acid sequence of the mature gene Bacillus sp G1 showed the highest homology of 98.3%, with 95% identity to alkalophilic Bacillus sp 1-1. The three catalytic residues Asp221, Glu249 and Asp320 in conserved regions II, III and IV respectively was found in CGTase from Bacillus sp. G1. 11 strictly conserved residues of the raw-starch binding motif were also found in Domain E. Some of the key residues and regions to product specificity are identified which are Tyr188, His47, Phe252, 38ETNPNY44 and 82HP---SGY85. The recombinant CGTase was expressed in the same pUC19 vector in E.coli and partially purified with ammonium sulphate precipitation. The optimum pH and temperature of the partially purified recombinant CGTase were 6.0 and 60oC. The pH stability was from pH 7.0 to pH 9.0 and the activity was retained up to 50oC after 30 minutes incubation at pH 6.0 in 0.1 M phosphate buffer without any substrate. The partially purified recombinant CGTase was able to prolong its thermal stability up to 60oC in the presence of 20 mM Ca2+. The CGTase was strongly inhibited by Zn2+, Cu2+, Co2+, Fe2+ and Fe3+. The CGTase produced - and -CD in a ratio of 0.11: 0.89 to total CD produced from 50 g/l tapioca starch after 24 hours incubation at 60oC, without adding any selective agents. The amount of -CD produced was 3.79 g/l. The partially purified CGTase from the recombinant E.coli retained properties quite similar to those of the wild type CGTase Bacillus sp. G1 in terms of molecular mass, reaction conditions, stability and the production of cyclodextrins.